Passing It On - Walter W. Powell (Sociologica)
This essay reflects on experiences with extraordinary mentors and decades of experience as a mentor. Mentorship is not about imparting knowledge top-down, but about creating an environment where people feel comfortable to ask hard questions and learning flows in multiple directions.